No direct nuclear effect of progesterone in the inner ear: other possible pathways. (December 2013) - Bonnard, Åsa; Sahlin, Lena; Hultcrantz, Malou; Simonoska, Rusana
Abstract Conclusion: No nuclear progesterone receptors were found in human or rat stria vascularis, organ of Corti or spiral ganglion with immunohistochemistry or polymerase chain reaction (PCR). Progesterone receptor B (PR-B) was found with Western blot in the cochlea, probably representing the staining in the cochlear bone. The effect of progesterone on hearing is therefore most likely not due to a direct action on the inner ear. Objectives: Studies suggest that progesterone as a component in hormone replacement therapy has a negative effect on hearing thresholds and otoacoustic emissions in pre- and postmenopausal women and mice. This study was designed to examine the presence of PRs in the cochlea of humans and rats. Methods: Immunohistochemical staining of PR protein in humans and rats, PCR of PR-B mRNA expression, and Western blot of PR-A and PR-B protein in rats was performed. Results: No nuclear staining could be found for any PR in human or rat inner ear except the PR-B staining in the cochlear bone. No mRNA expression was detected by PCR. PR-B could be detected in Western blot performed on the whole cochlea including bone.